Efektivitas Aplikasi LAPOR Dinas Komunikasi dan Informatika dalam Menjaring Aspirasi Masyarakat - Jamaluddin Fawaid; Hariyanto, Didik (LPPM Stikosa - AWS, 2023)
LAPOR namely an application for public complaints is one of the steps taken by the central government to anticipate the need for feedback from the public on the services provided by the government. Feedback in providing services is important because it can be a material for improvement for Sidoarjo Regency Government agencies. The benefits of conducting research are to find out the effectiveness of the application of LAPOR, as well as to find out what factors are the strengths, weaknesses, opportunities, and threats in implementing LAPOR in Sidoarjo. This research refers to the theory of Organization Public Relationship (OPR). This study uses a qualitative method with a descriptive approach, with the subject being the focus of the Sidoarjo Regency Communication and Information Service, while the object is the People's Online Aspirations and Complaints Service (LAPOR). The results of this study show that the LAPOR application involves public participation and increases two-way interaction between the community and the government in overseeing development programs. This has proven to be effective from the 2023 reports for January and February which show that there are relatively many complaints coming in, and the average number of complaints in that month is road infrastructure. The application of LAPOR in the city of Sidoarjo may face several obstacles, including limited access and understanding of technology, not all people have adequate access to the internet or the devices needed to use the LAPOR application.